Optical properties of titanium-doped lithium niobate from time-dependent density-functional theory - Friedrich, Michael; Schmidt, Wolf Gero; Schindlmayr, Arno; Sanna, Simone (Physical Review Materials)
The optical properties of pristine and titanium-doped LiNbO3 are modeled from first principles. The dielectric functions are calculated within time-dependent density-functional theory, and a model long-range contribution is employed for the exchange-correlation kernel in order to account for the electron-hole binding. Our study focuses on the influence of substitutional titanium atoms on lithium sites. We show that an increasing titanium concentration enhances the values of the refractive indices and the reflectivity.

Consistent atomic geometries and electronic structure of five phases of potassium niobate from density-functional theory - Schmidt, Falko; Landmann, Marc; Rauls, Eva; Argiolas, Nicola; Sanna, Simone; Schmidt, Wolf Gero; Schindlmayr, Arno (Advances in Materials Science and Engineering)
We perform a comprehensive theoretical study of the structural and electronic properties of potassium niobate (KNbO3) in the cubic, tetragonal, orthorhombic, monoclinic, and rhombohedral phase, based on density-functional theory. The influence of different parametrizations of the exchange-correlation functional on the investigated properties is analyzed in detail, and the results are compared to available experimental data. We argue that the PBEsol and AM05 generalized gradient approximations as well as the RTPSS meta-generalized gradient approximation yield consistently accurate structural data for both the external and internal degrees of freedom and are overall superior to the local-density approximation or other conventional generalized gradient approximations for the structural characterization of KNbO3. Band-structure calculations using a HSE-type hybrid functional further indicate significant near degeneracies of band-edge states in all phases which are expected to be relevant for the optical response of the material.

Planning with Independent Task Networks - Mohr, Felix; Lettmann, Theodor; Hüllermeier, Eyke (Proc. 40th Annual German Conference on Advances in Artificial Intelligence (KI 2017))

Was ist Synthese? - Ficara, Elena (Fatum Magazin)

A Compensation Method for Production Tolerances in Electric Drive Systems Using an Extended Open-Loop Torque Control - Ott, Markus; Beckmann, Alexander; Böcker, Joachim (European Battery, Hybrid and Fuel Cell Electric Vehicle Congress Geneva, 14th-16th March 2017)

Scotts Institutionenbegriff als Heuristik zur Analyse von Geschlechterverhältnissen in Organisationen: Inspirationsquelle „Geschlechterwissen - Horwath, Ilona (Scotts Institutionenbegriff Als Heuristik Zur Analyse von Geschlechterverhältnissen in Organisationen: Inspirationsquelle „Geschlechterwissen,)

Modellbasierte Mehrzieloptimierung zur Herstellung von Ultraschall-Drahtbondverbindungen in Leistungshalbleitermodulen - Unger, Andreas
Das Ultraschall-Drahtbonden mit Aluminiumdraht ist aktuell ein Standardverfahren zur Kontaktierung von Leistungshalbleitermodulen. Jedoch soll die Einführung von Kupferdraht als Bondmaterial in der Zukunft zu zahlreichen Verbesserungen der Module führen. Dies ist bedingt durch die wesentlich besseren elektrischen und thermischen Eigenschaften von Kupfer gegenüber Aluminium, die dazu führen, dass z. B. eine weitere Miniaturisierung elektrischer Komponenten möglich wird. Darüber hinaus könnte insbesondere die Verlässlichkeit der Module signifikant verbessert werden. Doch bisher wurde Kupferdraht trotz seiner überlegenen physikalischen Eigenschaften im Wesentlichen nur vereinzelt eingesetzt, da der Prozess deutlich empfindlicher auf Störgrößen reagiert. Um dennoch zuverlässige Kupferbondverbindungen in Leistungshalbleitermodulen herstellen zu können, wird in dieser Arbeit ein Verfahren vorgestellt, das die Herstellung von Ultraschall-Bondverbindungen mittels modellbasierter Mehrzieloptimierung realisiert. Dazu ist umfangreiches Prozesswissen in Form eines geeigneten Modells für den Bondprozess notwendig. Das vorgestellte Modell ist in der Lage, alle notwendigen Effekte und den Einfluss wesentlicher Prozessparameter detailliert abzubilden, sodass eine anschließende Mehrzieloptimierung zur Bestimmung der pareto-optimalen Betriebspunkte und zugehörigen Prozessparameter ermöglicht wird. Die dafür notwendigen Teilmodelle und Mehrzieloptimierungen werden dargestellt und validiert. Überdies wird ein Prototyp in Form einer modifizierten Bondmaschine inklusive einer Möglichkeit zur Verhaltensanpassung aufgebaut und getestet.
Keywords: Drahtbondverbindungen

Bergès, Sandrine; Coffee, Alan (Eds.). The Social and Political Philosophy of Mary Wollstonecraft. Oxford University Press, 2017. - Hagengruber, Ruth Edith

Religion und Politik im Röhrentruper Rezeß von 1617. [Laudatio auf Johannes Stüer.] - Süßmann, Johannes (Neujahrsempfang der Universität Paderborn 15. Januar 2017. Laudationes)

Editorial: Reclaiming Quality Development: Forschung über Lehre und Studium als Teil der Qualitätsentwicklung - Steinhardt, Isabel; Pohlenz, Philipp; Merkt, Marianne (Zeitschrift für Hochschulentwicklung)

The Multifaceted Nature of Agency and Professional Learning - Paloniemi, Susanna; Goller, Michael (Agency at work: An agentic perspective on professional learning and development)
The present volume has aimed to cover a broad range of approaches to agency at work, exploring its relationship with professional learning and development. Thus, the chapters included in this book have discussed the role of agency in learning and development, considering a variety of working life contexts and applying both conceptual and empirical perspectives. This final chapter provides an overview of both the conceptual approaches and the empirical implementations. We see the perspectives as complementary. From the content of the book, we discern the phenomena as falling on two main dimensions, clustering at opposite ends of these dimensions. Thus, the following contrasts are evidenced: (a) agency understood as a personal capacity, vs. agency as behaviour, and (b) agency as an individual phenomenon, vs. agency as a collective phenomenon. All the chapters emphasise that agency is needed for learning and development. However, they differ in how they view the relationships between the concepts. They also exhibit differences in the empirical decisions taken and the research strategies chosen. In this concluding chapter, we discuss the main similarities and differences emerging from the chapters. We also highlight avenues for future research on agency and its relationship with professional learning.
Keywords: Agency; Workplace learning; Professional development

Schnittstellenaufgaben für die Analysis I – Konzept, Beispiele und Evaluationsergebnisse - Hoffmann, Max; Biehler, Rolf (Beiträge zum Mathematikunterricht 2017)

The interplay between subjective abilities and subjective demands and its relationship with academic success. An application of the person–environment fit theory - Bohndick, Carla; Rosman, Tom; Kohlmeyer, Susanne; Buhl, Heike M. (Higher Education)
In this study, we draw on person–environment fit theory to analyze whether academic success is best explained by individual abilities subjectively exceeding situational demands or by abilities matching the demands. Moreover, we disentangled effects of perceived abilities and subjective person–environment (P-E) fit on academic success. All in all, 693 teacher education students participated in an online questionnaire. Students were asked to rate general requirements of their academic programs (e.g., self-discipline) on a 5-point scale in terms of (1) their own abilities and (2) the perceived relevance for their studies. P-E fit was determined by difference scores between abilities and relevance ratings. Academic success was assessed by grades, perceived performance, and study satisfaction. Data were analyzed through structural equation modeling and suggest that academic success is best explained by a match between abilities and demands. Moreover, all three criteria for academic success were more strongly related to subjective fit than to subjective abilities.
Keywords: Academic success; Person–environment fit theory; Demands–abilities fit; Higher education

Bildung und Lesesozialisation im Elternhaus - Buhl, Heike M.; Hilkenmeier, Johanna (Handbuch Entwicklungs- und Erziehungspsychologie)
Deutliche Unterschiede im Bildungserfolg von Kindern abhängig vom familialen Hintergrund zeigen, dass, ungeachtet der schulischen Bemühungen um die kindliche Bildung, die Familie weiterhin ein wesentlicher Einflussfaktor ist. Vor diesem Hintergrund werden im Folgenden die Wege erörtert, über die sich diese Einflüsse realisieren. Nach einem Überblick zu einschlägigen Prozessen werden in diesem Beitrag familiale Wirkungszusammenhänge am Beispiel der Lesesozialisation genauer beleuchtet. Vor diesem Hintergrund werden abschließend Programme zur Förderung der familialen Unterstützung diskutiert.
Keywords: Lesesozialisation; Familiale Erziehung; Familienklima; Kindliche Bildung; Bildungserwartungen; Häusliche Anregung; Home literacy environment; Vorlesen; Literacy

Professionalism in parent-teacher conversations: Aspects, determinants, and consequences. A competence-oriented discussion - Buhl, Heike M.; Hilkenmeier, Johanna (Journal of Educational Research Online)

Editorial Gespräche zwischen Eltern und Lehrkräften - Buhl, Heike M.; Hilkenmeier, Johanna (Psychologie in Erziehung und Unterricht)
Keywords: Developmental and Educational Psychology

Grammatikerwerb und grammatische Störungen im Kindesalter. Ergebnisse des Forschungsprojekts GED 4-9 und ihre Implikationen für sprachdiagnostische und - therapeutische Methoden - Ulrich, Tanja

Linking Services to Websites by Leveraging Semantic Data - Wolters, Dennis; Heindorf, Stefan; Kirchhoff, Jonas; Engels, Gregor (2017 IEEE International Conference on Web Services (ICWS))
Websites increasingly embed semantic data for search engine optimization. The most common ontology for semantic data, schema.org, is supported by all major search engines and describes over 500 data types, including calendar events, recipes, products, and TV shows. As of today, users wishing to pass this data to their favorite applications, e.g., their calendars, cookbooks, price comparison applications or even smart devices such as TV receivers, rely on cumbersome and error-prone workarounds such as reentering the data or a series of copy and paste operations. In this paper, we present Semantic Data Mediator (SDM), an approach that allows the easy transfer of semantic data to a multitude of services, ranging from web services to applications installed on different devices. SDM extracts semantic data from the currently displayed web page on the client-side, offers suitable services to the user, and by the press of a button, forwards this data to the desired service while doing all the necessary data conversion and service interface adaptation in between. To realize this, we built a reusable repository of service descriptions, data converters, and service adapters, which can be extended by the crowd. Our approach for linking services to websites relies solely on semantic data and does not require any additional support by either website or service developers. We have fully implemented our approach and present a real-world case study demonstrating its feasibility and usefulness.
Keywords: Services; Websites; Semantic Data; schema.org; Data Conversion; Interface Adaptation; Mediation

Overview of the Wikidata Vandalism Detection Task at WSDM Cup 2017 - Heindorf, Stefan; Potthast, Martin; Engels, Gregor; Stein, Benno (WSDM Cup 2017 Notebook Papers)
We report on the Wikidata vandalism detection task at the WSDM Cup 2017. The task received five submissions for which this paper describes their evaluation and a comparison to state of the art baselines. Unlike previous work, we recast Wikidata vandalism detection as an online learning problem, requiring participant software to predict vandalism in near real-time. The best-performing approach achieves a ROC-AUC of 0.947 at a PR-AUC of 0.458. In particular, this task was organized as a software submission task: to maximize reproducibility as well as to foster future research and development on this task, the participants were asked to submit their working software to the TIRA experimentation platform along with the source code for open source release.

Rheinland-Pfalz: Ein Bundesland auf dem Weg zu schulischer Inklusion? - Scheer, David; Laubenstein, Désirée; Lindmeier, Christian; Guthöhrlein, Kirsten; Sponholz, Dirk (Zeitschrift für Inklusion-Online, Nr. 2)

Zugänge zur Erfassung der Schreibkompetenzen von Studierenden in lehrnahen Untersuchungen: Ein Methodenkompass - Scharlau, Ingrid; Golombek, Christiane; Klingsieck, Katrin B. (die hochschullehre)
Ziel dieses Beitrags ist die Vorstellung und Diskussion unterschiedlicher Methoden zur Erfassung von hochschulischen Lernprozessen. Den konzeptuellen Rahmen dafür bietet das Scholarship of Teaching and Learning (SoTL). Am Beispiel von Schreibkompetenzen werden Analysen von Textproben, Selbsteinschätzungen per Fragebogen und Interview, Protokolle lauten Denkens und standardisierte Testverfahren vorgestellt. Die Vor- und Nachteile jeder Methode werden anhand exemplarischer Fragestellungen diskutiert. Abschließend reflektiert der Beitrag die Frage, wie SoTL von Überlegungen aus mixed-methods-Ansätzen profitieren kann.

Dimensionen inklusionsbezogener Fortbildungsmotivation von Sonderpädagoginnen und Sonderpädagogen und Lehrkräften allgemeiner Schulen - Gorges, Julia; Neumann, Phillip; Lütje-Klose, Birgit; Wild, Elke (Empirische Sonderpädagogik)
In der vorliegenden Studie wird die konzeptuelle Binnenstruktur der Fortbildungsmotivation von Sonderpädagoginnen und Sonderpädagogen und Lehrkräften allgemeiner Schulen (N=287) mit Blick auf eine inklusionsbezogene Fortbildung zur multiprofessionellen Kooperation aus Perspektive der Erwartungs-Wert-Theorie untersucht. Konfirmatorische Faktorenanalysen zeigen eine 4-Komponenten-Struktur des subjektiven Wertes. Teilnahmeförderliche Wertüberzeugungen, die mithilfe von Items mit intrinsischer, utilitaristischer und persönlicher Ausrichtung erfasst wurden, lassen sich nach den Bezugspunkten Inhalt, Status als Teilnehmerin oder Teilnehmer und Abschluss untergliedern. Eine Kostenkomponente mit monetären und nicht-monetären Anteilen bildet einen eigenständigen Faktor. Der 4-faktorielle subjektive Wert lässt sich weiterhin von einem Bilanzwert abgrenzen, der ein Gesamturteil hinsichtlich der untersuchten Fortbildung reflektiert und primär von inhaltsbezogenen Wertkomponenten sowie der Kostenkomponente des Wertes vorhergesagt wird. Es zeigen sich professionsbezogene Unterschiede sowohl bei der Höhe der Werteinschätzungen als auch bei deren Zusammenspiel zur Bestimmung des Bilanzwertes. Die Diskussion thematisiert theoretische und praktische Implikationen der Befunde.
Keywords: Erwartungs-Wert-Theorie; Inklusion; Lehrerfortbildung; Motivation; multiprofessionelle Kooperation; subjektiver Aufgabenwert; BiFoKi

Schulische Inklusion in Nordrhein-Westfalen (NRW) – sieben Jahre nach Ratifizierung der UN-BRK - Lütje-Klose, Birgit; Neumann, Phillip; Streese, Bettina (Zeitschrift für Inklusion)
Birgit Lütje-Klose, Phillip Neumann und Bettina Streese ziehen für Nordrhein-Westfalen Bilanz nach sieben Jahren ratifizierter UN-BRK. Ziel der seit 2010 bestehenden rot-grünen Landesregierung ist es (schul-)gesetzliche Veränderungen auf den Weg zu bringen, die die Dominanz der exklusiven Beschulung von Kindern und Jugendlichen mit sonderpädagogischen Unterstützungsbedarfen überwinden. Gewürdigt werden die finanziellen, konzeptionellen und gesetzgeberischen Maßnahmen. Die Autor*innen machen jedoch auf zahlreiche Rekontextualisierungsprozesse im Entwicklungsverlauf aufmerksam, die strukturell-oragnisatorisch dür die einzelne Schule, wie auf der Ebene des Unterrichts spürbar werden. “Dem Land ist letztlich Mut zu wünschen für politische Beschlüsse, die Doppelstrukturen abbauen und einen gezielteren Einsatz der finanziellen und personellen Ressourcen ermöglichen würden”.

Bielefelder Längsschnittstudie zum Lernen in inklusiven und exklusiven Förderarrangements (BiLieF). Technical Report - Wild, Elke; Lütje-Klose, Birgit; Schwinger, Malte; Gorges, Julia; Neumann, Phillip

Leistung inklusive? Inklusion in der Leistungsgesellschaft. Band I: Menschenrechtliche, sozialtheoretische und professionsbezogene Perspektiven

Leistung inklusive? Inklusion in der Leistungsgesellschaft. Zur Einführung in Band I - Lütje-Klose, Birgit; Boger, Julia Mai-Anh; Hopmann, Benedikt; Neumann, Phillip (Leistung inklusive? Inklusion in der Leistungsgesellschaft. Band I: Menschenrechtliche, sozialtheoretische und professionsbezogene Perspektiven)

Pleasing Little Sister. Big Data und Social Media Surveillance - Weber, Jutta (Bedeutende Daten. Modelle, Verfahren und Praxis der Vermessung und Verdatung im Netz)

Byzanz um 1200 - Becker, Rieke (Handbuch zur Mittelalternumismatik)

Feministische STS. Einführung - Weber, Jutta (Science and Technology Studies – Klassische Positionen und aktuelle Perspektiven)

Tracking and Targeting: Sociotechnologies of (In)security. Special Issue of ‘Science, Technology & Human Values’ (Science, Technology & Human Values)

Information Technology and Sustainability in the Information Society - Fuchs, Christian (International Journal of Communication)

Fascism 2.0: Twitter Users’ Social Media Memories of Hitler on his 127th Birthday - Fuchs, Christian (Fascism: Journal of Comparative Fascist Studies)

Preface: Horst Holzer’s Marxist Theory of Communication [Preface to Christian Fuchs’ translation of Horst Holzer’s article “The Forgotten Marxist Theory of Communication & Society“] - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

The Relevance of Franz L. Neumann’s Critical Theory in 2017: “Anxiety and Politics“ in the New Age of Authoritarian Capitalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Günther Anders’ Undiscovered Critical Theory of Technology in the Age of Big Data Capitalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Die Kritik der Politischen Ökonomie der Medien/Kommunikation: ein hochaktueller Ansatz - Fuchs, Christian (Publizistik)

YouTube’da reklamlar faşizmle buluşunca: Yeni Google skandalı bize büyük veri kapitalizmi hakkında ne söylüyor? - Fuchs, Christian (Sendika.org)

When Ads Meet Fascism On YouTube: What The Recent Google-Scandal Tells Us About Big Data Capitalism (Long version) - Fuchs, Christian (Medium.com)

When Ads Meet Fascism On YouTube: What The Recent Google-Scandal Tells Us About Big Data Capitalism (Short version) - Fuchs, Christian (Huffington Post)

Generation and active manipulation of qubits in LiNbO3-based integrated circuits - Meier, Torsten; Sharapova, P.R.; Luo, K.H.; Herrmann, H.; Reichelt, Matthias; Silberhorn, C. (arXiv preprint arXiv:1704.03769)

Hacia un estudio Marxiano del Internet. Translated by Adrián Montero Morera - Fuchs, Christian (Revista de Ciencias Sociales Universidad de la Universidad de Costa Rica)

Fake News Is Not Just The Word Of The Year, But A Danger To Democracy That Can Only Be Overcome By Adequate Legal And Media Reforms - Fuchs, Christian (Huffington Post)

What is to Be Done? The Role of the New and the Old in Media Theory – The Moment for Critical Digital and Social Media Studies - Fuchs, Christian (Westminster Papers in Communication and Culture)

Donald Trump: A Critical Theory-Perspective on Authoritarian Capitalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

How the Frankfurt School Helps Us to Understand Donald Trump’s Twitter Populism - Fuchs, Christian (The Huffington Post)

Towards the Public Service Internet as Alternative to the Commercial Internet - Fuchs, Christian (ORF Texte No. 20 – Öffentlich-Rechtliche Qualität im Diskurs)

Written Evidence Submitted to the House of Commons-Digital, Culture, Media and Sport Select Committee’s Inquiry on Fake News. Published on November 28, 2017 - Fuchs, Christian

Organic Polymers as Porogenic Structure Matrices for Mesoporous Alumina and Magnesia - Chen, Zimei; Weinberger, Christian; Tiemann, Michael; Kuckling, Dirk (Processes)
Dimethylacrylamide-based hydrogels were utilized as porogenic matrices in the synthesis of mesoporous aluminum oxide (γ-Al2O3) with specific BET surface areas up to 360 m2 g–1. Polymers with molecular mass in the range 12000–35000 g mol–1 were synthesized from dimethylacrylamide and various comonomers by free-radical polymerization. Photo-cross-linking of the polymers and impregnation with aluminum nitrate [Al(NO3)3] was carried out in a single step, followed by formation of Al(OH)3/AlO(OH) and subsequent calcination. Calcination led to the formation of mesoporous Al2O3 and simultaneous combustion of the hydrogel. The structural properties of the products were characterized by powder XRD, N2 physisorption analysis, Hg intrusion porosimetry, and thermogravimetric analysis.

Exkursinhalte in der fachmathematischen Lehramtsausbildung: Wie man das Wesen und die Rolle der Mathematik vermittelt. - Weich, Tobias; Hoffmann, Max (die hochschullehre)

A. Voß: Reisen erzählen. Erzählrhetorik, Intertextualität und Gebrauchsfunktionen des adligen Bildungsreiseberichts in der Frühen Neuzeit. Heidelberg 2016 - Moritz, Tilman (DIEGESIS)